2018
DOI: 10.1002/adsc.201800012
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Oxidative Carbamoylation of N‐Arylacrylamides with Hydrazinecarboxamides Leading to 2‐(Oxindol‐3‐yl)acetamides

Abstract: A tandem radical carbamoylation/cyclization reaction of N‐arylacrylamides with hydrazinecarboxamides has been developed for facile access to 2‐(oxindol‐3‐yl)acetamides, which had been utilized as precursors in the synthesis of natural bioactive pyrrolidinoindolines. In the presence of 1 mol% of copper(II) carbonate and 4 equiv. of tert‐butyl hydroperoxide, a wide range of N‐arylacrylamides underwent highly regioselective carbamoylation with hydrazinecarboxamides followed by 5‐exo‐trig cyclization to afford str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 67 publications
0
16
0
1
Order By: Relevance
“…Based on the above experimental results and previous reports, [16] a possible reaction pathway was proposed as shown in Scheme 3. Firstly, carbamoyl radical 2 generated from the reaction of hydrazinecarboxamide with TBHP.…”
Section: As Show Inmentioning
confidence: 63%
See 2 more Smart Citations
“…Based on the above experimental results and previous reports, [16] a possible reaction pathway was proposed as shown in Scheme 3. Firstly, carbamoyl radical 2 generated from the reaction of hydrazinecarboxamide with TBHP.…”
Section: As Show Inmentioning
confidence: 63%
“…Although various reactions for the synthesis of quinoline derivatives have been realized, trying to develop new versatile and practical methods are still desirable. Recently, Tian's group realized carbamoylation of N ‐arylacrylamides and nitrogen heteroarenes using hydrazinecarboxamides as substrates . Encouraged by Tian's work and on the basis of our continued pursuit of C−H bond activation, herein we disclose a new strategy to access carbamoylated quinolone N ‐oxides via CuBr‐catalyzed carbamoylation of quinolone N‐oxides with hydrazinecarboxamides.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrosynthetic analysis indicated that the aforementioned valuable alkaloids share the same building block, 3-formyloxindoles (Figure ). Although considerable efforts for constructing 3-functional-oxindoles have been made, short synthesis of 3-formyloxindole structure from low-cost and readily available starting materials under mild conditions are rare. The formyl group provides a handle for chemical transformations because of its rich chemical reactivity .…”
mentioning
confidence: 99%
“…α,β-Unsaturated amides are an important structural motif that is present in a wide range of natural products, pharmaceuticals, and polymeric materials . Additionally, α,β-unsaturated amides also serve as versatile building blocks in organic synthesis . They are not only viable for further functionalization but also active for reactions such as nucleophilic addition and pericyclic reactions.…”
mentioning
confidence: 99%